Analisis Preferensi, Perilaku, dan Faktor yang Mempengaruhi Penggunaan Qris dalam Transaksi Digital di Kalangan Mahasiswa dan Pengguna Media Sosial : (Studi pada Mahasiswa UNPAB) - Mutia Anggraini; Rusiadi, Rusiadi (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study was carried out with the objective of examine the level of perception of the usefulness of QRIS, ease of use of QRIS, the influence of social media, and infrastructure & system support significantly contribute to the tendency of student preferences and preferences of social media users. This study adopts a quantitative approach as a framework in the analysis. The target population includes students from the Faculty of Social Sciences, Panca Budi Development University, which is divided into five study programs: Law, Management, Accounting, Development Economics, and Taxation, who also act as active users of social media. The sample consisted of 100 respondents selected using the Non Probability method through purposive sampling techniques. The data collection process was carried out by distributing survey instruments in the form of questionnaires. All data collected were analyzed using SPSS software, with stages of analysis including instrument testing, classical assumption testing, simultaneous regression analysis, and hypothesis testing as a form of statistical verification.